AB1181 ULTRASOUND PATHOLOGICAL PATTERNS AT CARPAL TUNNEL LEVEL IN RHEUMATOID ARTHRITIS AND IDIOPATHIC CARPAL TUNNEL SYNDROME. (June 2019) - Smerilli, Gianluca; Filippucci, Emilio; Matteo, Andrea DI; Draghessi, Antonella; Gasparini, Stefania; Incorvaia, Antonella; Carlo, Marco DI; Grassi, Walter
Abstract : Background: High-frequency ultrasound (US) has proven to be a useful imaging tool for the evaluation of carpal tunnel pathology. US impact in the assessment of idiopathic carpal tunnel syndrome (CTS) has been widely investigated, but only few studies have been carried out with the aim of revealing the pathologic conditions responsible for CTS in rheumatoid arthritis (RA) patients 1 . Objectives: The aim of this study is to evaluate US findings at carpal tunnel level in a cohort of patients with RA, focusing on those with a clinical diagnosis of CTS, and to compare these findings with those observed in a cohort of patients with idiopathic CTS (without RA). Methods: Fifty-six patients with RA fulfilling the ACR/EULAR 2010 classification criteria were consecutively enrolled. CTS was diagnosed according to the American Academy of Neurology practice parameter for CTS. We also enrolled 19 patients with idiopathic CTS and evaluated 24 symptomatic wrists, excluding those already surgically decompressed. The US assessment was performed using a MyLab ClassC (Esaote SpA) US system, working with a 6-18 MHz linear probe. The power Doppler (PD) frequency was set at 9.1 MHz. The following grey scale (GS) US pathologic findings were assessed at the carpal tunnel level: cross-sectional area (CSA) of the median nerve at the carpal tunnel inlet (at the level of the pisiform and scaphoid bones), presence of finger flexor tenosynovitis and palmar radio-carpal synovitis (both in GS and PD), and marked bone profile irregularities. The median nerve was considered enlarged if its CSA was more than 12 mm 2 . We evaluated the presence of intra-neural PD signals at the carpal inlet and scored its entity (0=no PD signal, 1=one single vessel within median nerve, 2=two or three single or two confluent vessels and 3=more than three single or more than two confluent vessels). Results: CTS was diagnosed in 21 out of 112 wrists (18.75%) and in 14 out of 56 RA patients (25%). Enlarged median nerve was found in 4 out of 21 wrists with RA and CTS (19%), in 6 out of 84 wrists of patients without CTS (7.1%) and in 22 out of 24 wrists of patients with idiopathic CTS (91.7%). Flexor tenosynovitis was found in 6 out of 21 wrists with RA and CTS (28.6%), in 8 out of 84 wrists of patients without CTS (8.2%) and in 4 out of 24 wrists with idiopathic CTS (16.7%). Palmar radio-carpal synovitis was found in 4 out of 21 wrists with CTS (19%), in 10 out of 84 wrists of patients without CTS (11.9%) and in 1 out of 24 wrists with idiopathic CTS (4.2%). Marked bone profile irregularities were detected in 3 out of 21 wrists with CTS (14.3%), in 22 out of 84 wrists without CTS (26.2%) and in none of the patients without RA. In RA patients, positive intra-neural PD signal was found in 9 out of 21 wrists with CTS (42.8%) and in 12 out of 84 wrists without CTS (14.3%). In idiopathic CTS, PD signal was found in 15 out of 24 wrists (62.5%). Conclusion: US allowed a detailed identification of the pathological findings at carpal tunnel in both RA and idiopathic CTS patients. When CTS was diagnosed, different US patterns were distinguished being median nerve less frequently enlarged and synovitis more frequently detected in RA patients. Finally, a positive association was found between the presence of intra-neural PD signal and clinical diagnosis of CTS independently of the diagnosis of RA. References: [1] Hammer HB, Hovden IA, Haavardsholm EA, Kvien TK. Ultrasonography shows increased cross-sectional area of the median nerve in patients with arthritis and carpal tunnel syndrome. Rheumatology (Oxford) 2006; 45(5):584-8. Disclosure of Interests: None declared